Revitalisasi Peran Masyarakat Adat dalam Penetapan dan Pengelolaan Taman Nasional Mutis-Timau - Jonsilas Tanaos; Eneng Nita Juwita (Universitas 17 Agustus 1945 Semarang, 2025)
Mutis Timau National Park is an important conservation area located in the South central Timor Regency, North Central Timor Regency and Kupang Regency, East Nusa Tenggara, which includes the customary areas of various local communities in West Timor-Indonesia. The establishment of this National Park gives a controversial impression from the indigenous people as stakeholders who have long lived, inherited, preserved and controlled the Mutis Timau area, the indigenous people feel that the consolidation in order to achieve a consensus between the indigenous people and the state, does not involve the indigenous people as a whole because of the fact that the indigenous people have historical and ecological values ​​​​attached to the area. This article discusses the importance of revitalizing the role of indigenous peoples in the process of establishing and managing Mutis Timau National Park through a participatory approach, recognition of customary rights and integration of local wisdom in conservation. Therefore, a more inclusive and collaborative state policy is needed to ensure the sustainability of the natural environment and social justice as a form of state recognition for indigenous peoples.